Penerapan Quantum Learning pada Materi Lingkaran di Kelas VIII SMP Muhammadiyah Palangka Raya Tahun 2018/2019 (JURNAL PENDIDIKAN, 2020)
This research aims to describe: 1). Activity of teacher and studentsby using Quantum Learning , 2) Achievement of students by using QuantumLearning, 3) Response of students by using quantum learning. Theinstruments were activity sheet of teacher and student, final test andquestionnaire. Based on the activity observation sheet shows the activities ofteachers and students were good. Individual test results at each meetingalso improved. At the first meeting the student achievement level was 78.91% and classical completeness was 91.30% with 21 students com. Atthe fourth meeting, the student achievement level was 88.77% and classicalcompleteness was 100% with 23 students who completed it. Studentachievement from final test that were given to 20 students, as many as 18students scored above the KKM (standard minimum achievement) withstudent achievement levels was 82.38% and classical learning completenesswas 90%. On the results of the questionnaire responses obtained an averageof 84.75% student answers with high criteria. In general students respondpositively about implemantion of the Quantum Learning during the learningprocess77.12% and classical learning completeness was 81.82% with 18 students.At the second and third meeting, the level of student achievement was